Peningkatan kemampuan guru dalam menerapkan model pembelajaran melalui kegiatan supervisi kelas MIN 13 Aceh Barat Daya - warni, Warni (Jurnal Pendidikan dan Pengabdian Vokasi (JP2V), 2020)
making use of learning models that are appropriate with the learning material. In general, teachers rarely use the learning model in each learning process, due to the lack of teacher understanding of learning models that can facilitate teachers in implementing the learning process in class. Actually there are many learning models that can be used by every teacher in the learning process. By using appropriate learning models, of course students will be motivated in learning, and this will have a positive impact on learning outcomes. The main problem in research, namely "Whether the application of learning models through classroom supervision activities can improve the quality of learning in students at MIN 13 Southwest Aceh? ". Based on the results of this study it was concluded that the application of learning models through classroom supervision by the school principal proved to be successful in increasing the ability of MIN 13 Aceh Barat Daya teachers to manage the learning process. In addition, with the increasing ability of MIN 13 Aceh Barat Daya teachers to manage the learning process, not only is the student learning process more meaningful but also the learning outcomes have improved.